Monocropping Degrades Soil Quality Index and Soil Multifunctionality Compared to Natural Grasslands and Restored Shrubland in China’s Qilian Mountains (Based on Single-Year Sampling) - Longji Zhang; Shaochong Wei; Hang Xiang; Xiaojun Yu (Agronomy)
As the ecological security barrier in northwestern China, understanding how natural grassland (NG) utilization pattern transformation in the northern Qilian foothills affects soil quality and ecosystem multifunctionality supports regional ecosystem management. The study compared soil chemical and biological properties, soil quality index (SQI), and soil ecosystem multifunctionality (SMF) among four grassland utilization patterns in the northern foothills of the Qilian Mountains, Gansu Province, China. Soil samples were collected in early October 2024 following crop harvest from the following systems: traditionally grazed NG, monocropping Hordeum vulgare (barley; MHV), monocropping Avena sativa (oat; MAS), and Hippophae rhamnoides shrubland (sea buckthorn; HRS). The results showed that compared with NG, SQI was decreased by 52.69% (p = 0.000059) under MHV treatment and by 18.78% (p = 0.03) under MAS treatment, while HRS did not have a significant reduction in SQI. Under the three patterns of transformative utilization of NG, SMF followed the order of HRS (0.11) > MAS (−0.06) > MHV (−0.51). Overall, the establishment of restoration vegetation (sea buckthorn shrubland) retained SQI under different grassland utilization patterns in the study area, whereas long-term monocropping resulted in significant reductions in SQI and SMF due to compromised chemical and biological properties.